Accountability for Financial Management of Village Funds by the Government of Kuteni Reje Village, Lut Tawar District, Central Aceh Regency - Rada Rispira, Fani; Koeswara, Hendri; Kabullah, Muhammad Ichsan (Pencerah, 2024)
Accountability in the financial management of Village Funds is crucial. This research is motivated by the financial management of village funds by the Kuteni Reje village government, which has achieved achievements in managing village funds. However, there are still shortcomings in implementing accountability in the financial management of Village Funds. Therefore, it is necessary to carry out a more in-depth study to find an accountability model for Village Fund management to maximize the performance of the Kuteni Reje village government as a public service provider. This research uses Mardiasmo's accountability theory, which consists of 4 (four) variables: legal accountability and honesty, process accountability, program accountability, and policy accountability. The research was conducted using qualitative methods. Data collection techniques were carried out using interviews and documentation. The selection of informants was carried out using a purposive sampling technique. The results of this research show that in terms of formal accountability, the management of Village Funds by the Kuteni Reje Village Government has been carried out accountably. However, there are still shortcomings in village financial management, namely delays in the process of preparing the Village Revenue and Expenditure Budget (APBK) and lack of transparent information regarding the Village Revenue and Expenditure Budget (APBK) to the community, especially the use of Village Funds, and the unavailability of compliant services for the community to convey any deviations in the management of Village Funds that occur. So, we need a model and pattern of accountability that focuses more on social accountability to complement the dark side of formal accountability so that the performance of the Village government in financial management becomes better.